Partial observer normal form for nonlinear system. (February 2016) - Tami, Ramdane; Zheng, Gang; Boutat, Driss; Aubry, Didier; Wang, Haoping
Abstract: In this paper, we investigate the estimation problem for a class of partially observable nonlinear systems. For the proposed Partial Observer Normal Form (PONF), necessary and sufficient conditions are deduced to guarantee the existence of a change of coordinates which can transform the studied system into the proposed PONF. Examples are provided to illustrate the effectiveness of the proposed results.